The migration phenomenon of Galicia: from migrant worker to friendly citizen… lessons learnt? - Malheiro Gutiérrez, Xosé Manuel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
In recent Galician history, emigration to the Americas has had great impact. Part of our present reality is informed by this phenomenon as it plays out in the economy, demographics, society, culture, education, and so on. Galicia,traditionally an exporter of manual workers (initially to the Americas, and then to Europe), continues to send off young, educated workers to other regions. Nonetheless, in some areas of Galicia there is a growing presence of immigrants, who are supplemented by returned emigrants.This study addresses the sociocultural patterns that tend to repeat them selves since the times of the departure of our grand parents to America, until today’s arrival in Galicia of immigrants from Central Europe, the Maghreb, SubSaharan Africa or LatinAmerica. It poses the question: Have we learned from our distant experience as immigrants in ways that can help us to understandand accept those who we now receive?
Keywords: Emigration; Immigration; Politics; Society; Education.